Neonatal Birthmarks at the 4 Central Hospitals in Vientiane Capital, Lao PDR - Vilounna Sanaphay MD; Sourideth Sengchanh MD; Alongkone Phengsavanh MD, PhD; Anousavanh Sanaphay MD, MPHM, PhD; Leelawadee Techasatian MD (SAGE Publishing, 2021)
Newborn skin disorders are quite common and happen to occur during the neonatal period. Most of the birthmarks are transient; however, worried parents often seek medical advice from their child's physician regarding skin lesions. Thus, it is important to differentiate the skin lesions from pathologic ones to avoid unnecessary diagnostic or therapeutic procedures. This is the first published study in Lao neonates that carried out the data from 4 central hospitals in Vientiane Capital, Lao PDR from September 2019 to February 2020. Among 500 neonates, Sebaceous gland hyperplasia (53%), Mongolian patches (46.6%), and Erythema toxicum neonatorum (30%) were the 3 most common cutaneous conditions found in the Lao newborns. From a clinical point of view, these findings are often a source of parental anxiety and medical concern for inexperienced clinicians.